Psychosocial factors associated with HbA1c in adults with insulin pump‐treated type 1 diabetes: a systematic review. Issue 9 (21st July 2020) - Schmidt, S.; Andersen Nexø, M.; Norgaard, O.; Willaing, I.; Pedersen‐Bjergaard, U.; Skinner, T. C.; Nørgaard, K.
Abstract: Aims: To identify currently available studies on the association between psychosocial factors and HbA1c in adults with insulin pump‐treated type 1 diabetes, by performing a systematic review of the literature. Methods: MEDLINE, Embase, CINAHL and PsycINFO were searched for original studies on the association between psychosocial factors and HbA1c in ≥ 50 adult, non‐pregnant, insulin pump users with type 1 diabetes. Results: The search resulted in 1777 unique records, of which eight were eligible for inclusion. All identified studies were observational, with sample sizes ranging from 51 to 214. Seven different psychosocial factors were investigated in the eight studies. Study analysis suggested that HbA1c may be associated with diabetes numeracy and quality of life. There were no indications of associations between HbA1c and fear of hypoglycaemia or self‐efficacy. Results regarding associations between HbA1c and coping style, diabetes distress and locus of control were inconsistent. Conclusions: This systematic review summarizes the currently limited information on the association between psychosocial factors and HbA1c during insulin pump therapy. The evidence base of the included studies was weak, and this review highlights the need for more research in these areas, with improved methodological and theoretical frameworks, including exploration of a broader spectrum of psychosocial variables and their potential association with HbA1c and other metabolic outcomes. (PROSPERO International prospective register of systematic reviews registration no: CRD42020145705). What's new?: The glycaemic benefits of insulin pump therapy vary among individuals, and the reasons for this are not fully clarified. This systematic review synthesizes the literature—eight observational studies in total—on the association between psychosocial factors and HbA1c in adult insulin pump users. Despite the importance of the topic for society as well as for the individual insulin pump wearer, research within this field is still limited in scope. More research is needed to fully elucidate what influences HbA1c during insulin pump therapy and what actions should be taken for more people to reach glycaemic goals.